Change in the Length of Life of Subarctic Jet Currents Over Iraq and their Impact on Drought - Al-Saadi, Zahraa Karim Jassim; Al-Asadi, Kadhim Abdul Wahhab (Journal of Posthumanism, 2025)
This article investigates the duration of subpolar jet stream persistence over Iraq and its impact on drought conditions. The research involves the analysis of synoptic weather maps at the 300-millibar level during the 0z nighttime observation for the years 1980–2024, focusing on the months of October, January, and April. The article calculates the temporal changes in jet stream persistence and analyses rainfall amounts during the same period and months to determine trends—whether increasing or decreasing. Furthermore, it explores the correlation between the duration of jet stream persistence and rainfall amounts to assess whether the relationship is positive (increasing) or negative (decreasing).